Mengoptimalkan Kemampuan Berpikir Kritis Matematis Siswa Menggunakan PJBL dengan Gallery Walk Technique Berbasis Tipe Kepribadian - Dera Amanda, Rizki; Suhendra, Suhendra; Hasanah, Aan (Jurnal Pendidikan Matematika : Judika Education, 2025)
This study aims to optimize students' mathematical critical thinking skills through the Project Based Learning (PjBL) model and the Gallery Walk technique, tailored to students' personality types based on the Thinking and Feeling dimensions of the Myers-Briggs Type Indicator (MBTI). The method used is qualitative with a case study approach on eighth-grade students at a junior high school in Bangka District, Bangka Belitung Islands Province. Data were collected through personality type questionnaires, observations, mathematical critical thinking tests, and interviews, then analyzed descriptively to evaluate the development of students' critical thinking abilities. The results indicate that the implementation of PjBL and Gallery Walk is effective in enhancing mathematical critical thinking skills, particularly in the aspects of interpretation, analysis, and solution evaluation. Students with the Thinking type excel in logical reasoning and structured analysis, while those with the Feeling type stand out in communication and group collaboration. The collaboration of these two personality types enriches the discussions and solutions produced. The study concludes that recognizing students' personality types and integrating project-based learning and active techniques like Gallery Walk are crucial to creating adaptive, effective, and meaningful mathematics learning.   Keywords: Gallery Walk, Mathematical Critical Thinking Skills, MBTI, Myers-Briggs Type Indicator, Project Based Learning, Qualitative